Pengaruh Media Pembelajaran Wordwall Terhadap Hasil Belajar Siswa Pada Materi Mengenal Alat Musik Daerah Kelas IV SDN 060826 Medan - Priono, Rizka Fadhilah; Aulia, Sri Mustika; Tambunan, Husna Parluhutan; Purnomo, Try Wahyu; Afriadi, Putra (Universitas Pahlawan Tuanku Tambusai, 2025)
Effective learning requires interesting and interactive media to improve students' understanding. One of the media that can be used is Wordwall, which offers game-based learning to improve learning motivation. This study aims to analyze the effect of using Wordwall on student learning outcomes in the material Getting to Know North Sumatra Regional Musical Instruments in class IV of SDN 060826 Medan. This study uses a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. The sample consisted of class IV A as the experimental class and class IV B as the control class. Data collection techniques include observation, learning outcome tests, and documentation. The results showed that 88.89% of students in the experimental class graduated after the posttest, compared to 75% in the control class. The t-test showed a significance value of 0.022 (<0.05), proving that Wordwall had a significant effect on student learning outcomes.